Biopolitical governance and identities - Dinesh, Jonathan (Nanyang Technological University, 2025)
This thesis aims to demonstrate how the colonial government of Hong Kong used education as a biopolitical tool to shape the attitudes of Hong Kong youth from 1950 to 1985. In particular, it will examine the educational institutions and ordinances employed to control and subjugate youth at the secondary and university levels through the lens of Michel Foucault, which will demonstrate how education and other institutions become means to discipline and control populations. Additionally, it will investigate the government’s efforts to collect data on the younger population through the City District Officer (CDO) Scheme of 1968, which led to the formation of intelligence committees. Utilising this study, I will employ underutilised archival evidence from the Hong Kong Public Records Office (HKPRO) and National Archives of the United Kingdom (TNA) and a mixture of existing primary sources, including legislative documents, Chinese school records, Central Intelligence Agency (CIA) and archives. Unofficial sources, notably Chinese and English newspapers that published remarks regarding colonial scholarship and education policies will also be analysed thoroughly. This will bolster the research in addressing the limitations of existing literature, which will address the power structure aspects of education that have shaped the minds of the youth.